An Analysis of Illocutionary Speech Acts in the Indonesian Minister of Primary and Secondary Education’s Speech at the UNESCO General Conference - Nur Athirah Syam; Muhammad Hasbi; Aslan Abidin (Journal of Social Research, 2026)
This study examines the illocutionary speech acts employed in the Indonesian Minister of Primary and Secondary Education's address at the UNESCO General Conference in November 2025, applying Searle's taxonomy of speech acts as the analytical framework. The analysis of 42 speech acts reveals that assertive utterances dominate the discourse, accounting for 47.62%, followed by commissives at 23.81%, expressives at 14.29%, directives at 11.90%, and declaratives at 2.38%. The findings demonstrate how diplomatic discourse strategically employs various speech acts to convey national positions, establish commitments, and maintain international relationships. This research contributes to understanding the pragmatic dimensions of diplomatic communication and the linguistic strategies employed by representatives of developing nations in multilateral forums.